ZDROWIE - CHOROBY NIE TYLKO W PRADZIEJACH - Gładykowska-Rzeczycka, Judyta Julia (Wydawnictwo Naukowe UAM, 2009)
A brief outline of health and diseases over the ages is presented herein based on written and iconographic sources, as well as on results of paleopathological studies. The article covers the earliest civilizations, chiefly of the Old World - Eurasia and Africa: the civilizations of China, India, Mesopotamia, Egypt, Greece, and the Roman Empire, as well as medieval and contemporary societies. The genesis and source (cradle) of some diseases, their dynamics, spread and influence on the fate of humans and nations are considered, examining their effect on socio-economic, political and cultural structures, and on science. The biological condition of human populations has been, and always is, inextricably linked to the state of the natural environment, in the broadest sense of this word. The growing (largely negative) impact of humans on the environment is increasingly clearly leading to its deterioration.
HEALTH - DISEASES IN PREHISTORY AND BEYOND